Clinical Course and Outcomes of Pediatric Tubercular Uveitis in North India. (18th August 2018) - Kaur, Savleen; Aggarwal, Kanika; Agarwal, Aniruddha; Suri, Deepti; Gupta, Anju; Singh, Ramandeep; Bansal, Reema; Singh, Surjit; Singh, Nirbhai; Gupta, Amod; Gupta, Vishali
ABSTRACT: Purpose : To analyze the clinical features, course, management, and outcomes of tubercular (TB) uveitis in the pediatric population and assess the response to anti-tubercular therapy (ATT). Methods : Hospital records of children (≤16 years) from a large tertiary-care institute between January 2001 and December 2015 were reviewed. Results : A total of 32 children (mean age: 10.7 ± 4.27 years; range 2–16) were diagnosed with TB-associated uveitis. The most common presentation was posterior uveitis ( n = 14, 43.75%) and panuveitis ( n = 14, 43.75%), followed by intermediate uveitis ( n = 2, 6.25%) and anterior uveitis ( n = 2, 6.25%); 14 children had probable intraocular tuberculosis (IOTB) (43.75%) and 17 (53.13%) had possible IOTB. Despite ATT and corticosteroids, 29.63% patients showed suboptimal response or worsening of disease requiring additional immunosuppression. Conclusions : TB is an important cause of pediatric uveitis in endemic countries. The manifestations of the disease resemble adult TB-related uveitis. However, higher inflammatory response in children may require more aggressive therapy with corticosteroids/immunosuppression.